Prenatal Stress and Low Birth Weight: Evidence from the Super Bowl - Brian Duncan; Hani Mansour; Daniel I. Rees (Institute for the Study of Labor (IZA), 2015)
Studies have estimated the relationship between psychological stress and birth weight by exploiting natural disasters and terrorist attacks, both of which could affect fetal health through other channels. Using data from the National Vital Statistics System for the period 1969-2004, we estimate the effect of prenatal exposure to the Super Bowl on low birth weight. Although major sporting events elicit intense emotions, they do not threaten viewers with direct physical harm or limit access to prenatal care. We find that Super Bowl exposure is associated with a small, but precisely estimated, increase in the probability of low birth weight.
Keywords: I12; J13; 330; low birth weight; Super Bowl; prenatal stress; tobacco use